1998
DOI: 10.1097/00004836-199804000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Development of Flat Adenoma and Superficial Rectal Cancer After Pelvic Radiation

Abstract: Little is known about the early development of rectal cancer in patients with radiation-induced colitis. We describe two patients with a history of radiation colitis who developed rectal cancer. The macroscopic appearance of these lesions suggested that they arose de novo, but the histologic findings were more consistent with progression along the adenoma-to-carcinoma sequence, a hybrid of de novo lesion and adenoma. Early rectal cancer associated with chronic inflammation should be considered if a nonpolypoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The pattern of development of a precursor lesion into cancer has substantial influence on the preventive effects of colonoscopy surveillance, and this pattern is unknown for CRCs that develop in HL survivors. Flat adenomas in the presence of chronic radiation colitis have been described in case reports on cancer survivors [ 16 , 17 ]. In addition, a recent review reported a high frequency of mucinous adenocarcinomas in case reports on radiotherapy-associated rectal cancer, suggesting a difference in tumor biology as compared with sporadic CRCs [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of development of a precursor lesion into cancer has substantial influence on the preventive effects of colonoscopy surveillance, and this pattern is unknown for CRCs that develop in HL survivors. Flat adenomas in the presence of chronic radiation colitis have been described in case reports on cancer survivors [ 16 , 17 ]. In addition, a recent review reported a high frequency of mucinous adenocarcinomas in case reports on radiotherapy-associated rectal cancer, suggesting a difference in tumor biology as compared with sporadic CRCs [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…They confirm that the development of normal mucosa into radiation-induced gastrointestinal adenocarcinomas is poorly investigated and hypothesize that cancer may arise from flat adenomas and/or an inflammatory background [3032]. A recent report showed a cumulative risk of 16.4 % for developing a subsequent primary cancer beyond 30 years after treatment for Wilms tumor; 41 % of these excess cancers, all treated with abdominal radiotherapy, were attributable to digestive cancer [16].…”
Section: Discussionmentioning
confidence: 85%